Enhancement of Antioxidative and Anti-Inflammatory Activities of Corn Silk Polysaccharides After Selenium Modification - Zheng YY; Tong XY; Zhang DY; Ouyang JM (Dove Medical Press, 2024)
Yu-Yun Zheng, Xin-Yi Tong, Da-Ying Zhang, Jian-Ming Ouyang Institute of Biomineralization and Lithiasis Research, College of Chemistry and Materials Science; Jinan University, Guangzhou, 510632, People's Republic of ChinaCorrespondence: Jian-Ming Ouyang, Email toyjm@jnu.edu.cnObjective: This study aimed to study the effect of selenium modification on the bioactivity of corn silk polysaccharides, particularly its antioxidant and anti-inflammatory functions.Methods: HNO3-NaSeO3 was used to selenize degraded corn silk polysaccharides (DCSP). The structure and physicochemical properties of DCSP and selenized corn silk polysaccharides (Se-DCSP) were characterized by inductively coupled plasma emission spectroscopy, Fourier-transform infrared, ultraviolet-visible spectroscopy, nuclear magnetic resonance, nanometer, scanning electron microscopy, and thermogravimetric analysis. The protective effects of DCSP and Se-DCSP on HK-2 cells damaged by nano-calcium oxalate and the changes of inflammatory factors were detected by laser confocal microscopy, flow cytometry, and fluorescence microscopy.Results: The selenium content of DCSP and Se-DCSP were 19.5 and 1226.7 μg/g, respectively. Compared with DCSP, Se-DCSP showed significantly improved biological activity, including the scavenging ability of various free radicals (increased by about 2- 3 times), the intracellular reactive oxygen content (decreased by about 1.5 times), and the mitochondrial membrane potential (decreased by about 2.5 times). Moreover, cell viability and morphological recovery ability were improved. Compared with DCSP, Se-DCSP significantly down-regulated HK-2 cell inflammatory factors MCP-1 (about 1.7 times), NLRP3, and NO (about 1.5 times).Conclusion: The antioxidant activity and the ability to down-regulate the expression of inflammatory factors of Se-DCSP were significantly enhanced compared with DCSP, and Se-DCSP can better protect HK-2 cells from oxidative damage, indicating that Se-DCSP has a stronger potential ability to inhibit kidney stone formation. Keywords: selenization, corn silk polysaccharide, antioxidant, cell protection, inflammation